An Analysis of Elementary School Students' Understanding of Mathematical Concept - Pratama, Maya Adina; Yurniwati, Yurniwati; Chaeruman, Uwes Anis (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to determine the understanding of the mathematical concepts of elementary school students infraction material. The subjects in this study were fourth-grade students at three elementary schools in Tanjung Aman District, Kotabumi, North Lampung, with 18 students. Data collection techniques were used in the form of interviews and tests. The data analysis technique used is descriptive qualitative analysis. The results of this study indicate that the average score of concept understanding is 30.2%. Based on the results of interviews and tests, it was found that students' understanding of mathematical concepts at the three elementary schools was still low.